2020
DOI: 10.1136/rapm-2019-101154
|View full text |Cite
|
Sign up to set email alerts
|

Cervical erector spinae plane block: a cadaver study

Abstract: BackgroundCervical erector spinae plane (ESP) block has been described to anesthetize the brachial plexus (BP), however, the mechanism of its clinical effect remains unknown. As the prevertebral fascia encloses the phrenic nerves, BP and erector spinae muscles to form a prevertebral compartment, a local anesthetic injected in the cervical ESP could potentially spread throughout the prevertebral compartment. This study utilizes cadaveric models to evaluate the spread of ESP injections at the C6 and C7 levels to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 12 publications
1
33
0
Order By: Relevance
“…However, in a cadaver study, when 20 mL dye mixture was injected at the C6 or C7 level, the phrenic nerve was stained by 3 of 10 injections. [ 8 ] In our case, phrenic nerve and brachial plexus block were observed in 1 (case 1) of 2 patients who had an excellent analgesic effect. For this reason, we believe that ESPB at the C7 level may be more likely to cause diaphragmatic paralysis.…”
Section: Discussionmentioning
confidence: 50%
“…However, in a cadaver study, when 20 mL dye mixture was injected at the C6 or C7 level, the phrenic nerve was stained by 3 of 10 injections. [ 8 ] In our case, phrenic nerve and brachial plexus block were observed in 1 (case 1) of 2 patients who had an excellent analgesic effect. For this reason, we believe that ESPB at the C7 level may be more likely to cause diaphragmatic paralysis.…”
Section: Discussionmentioning
confidence: 50%
“…24 A final consideration is that extent of dye spread is determined by macroscopic visual inspection of the results of dissection or imaging, and more subtle boundaries of spread may not be evident. In some cadaveric studies, a distinction is made between heavy or faint dye staining of nerves, 25 but it is unclear how this correlates with anesthetic effect in living subjects. As will be discussed, even very low concentrations of local anesthetic in the vicinity of a nerve may exert a physiologic effect.…”
Section: Considerations In Cadaveric Studiesmentioning
confidence: 99%
“…93 Similarly, cadaveric injection at the C6 and C7 level consistently produced staining of the C5-C8 nerve roots, as well as the suprascapular, dorsal scapular, and long thoracic nerves that innervate the shoulder girdle. 25…”
Section: Physical Local Anesthetic Spread At Lumbar Vertebral Levelsmentioning
confidence: 99%
“…8,9 A cadaveric study using injections of MBD dorsal to C6 TP demonstrated consistent stain of ventral nerve roots in all specimens and phrenic nerve in one specimen. 11 The study involved injection and dissection in a prone position and then repositioned to supine followed by anterior dissection. This could lead to the spread of dye to unwanted areas affecting the analysis.…”
Section: Discussionmentioning
confidence: 99%